Dr. André Auersvald — Deep Plane Facelift - Auersvald, André (DEEPPLANE™, 2026)
Surgeon profile record for Dr. André Auersvald, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003097; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil